Is green the new grey? : Critical view on the impact of green solutions in construction industry - Zima, Filip (2021)
The thesis performs a descriptive practice-oriented scientific case study investigation into a contemporary issue of sustainability in the construction industry. The author blends a scientific perspective on case study research with best practices gleaned from well-known non-research educative and commercial case studies to produce a case study research with adequate scientific rigor and comprehensive reports to reinforce teaching and learning. In the theoretical part, the author provides a concise summary of the essential knowledge and practical processes for students to undertake a case study research in business. In the practical section, the thesis employs the recommended case study design and selects methodologies (expert interviews, literature review, field observations) in order to derive best practices in critical product assessment from a case of a Czech construction firm that designed and produced green facades as a sustainable solution to mitigate the effects of climate change.